2022
DOI: 10.1177/03000605221097490
|View full text |Cite
|
Sign up to set email alerts
|

Luseogliflozin inhibits high glucose-induced TGF-β2 expression in mouse cardiomyocytes by suppressing NHE-1 activity

Abstract: Objective Sodium-glucose cotransporter-2 (SGLT2) inhibitors exhibit cardioprotective properties in patients with diabetes. However, SGLT2 is not expressed in the heart, and the underlying molecular mechanisms are not fully understood. We investigated whether the SGLT2 inhibitor luseogliflozin exerts beneficial effects on high glucose-exposed cardiomyocytes via the suppression of sodium-hydrogen exchanger-1 (NHE-1) activity. Methods Mouse cardiomyocytes were incubated under normal or high glucose conditions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“… 66 , 67 The published interchange between the 2 groups revealed that the data of Chung et al 69 were derived from a larger sample size. 68 , 69 Osaka et al 70 claimed that SGLT2 inhibition inhibited NHE1, but the effect was substantially less than that seen with cariporide. Li et al 48 failed to show meaningful docking of empagliflozin to NHE1 and reported that cariporide did not mimic the action of the SGLT2 inhibitor on isolated cardiomyocytes.…”
Section: Potential Actions Of Sglt2 Inhibitors To Inhibit Sodium-hydr...mentioning
confidence: 99%
“… 66 , 67 The published interchange between the 2 groups revealed that the data of Chung et al 69 were derived from a larger sample size. 68 , 69 Osaka et al 70 claimed that SGLT2 inhibition inhibited NHE1, but the effect was substantially less than that seen with cariporide. Li et al 48 failed to show meaningful docking of empagliflozin to NHE1 and reported that cariporide did not mimic the action of the SGLT2 inhibitor on isolated cardiomyocytes.…”
Section: Potential Actions Of Sglt2 Inhibitors To Inhibit Sodium-hydr...mentioning
confidence: 99%
“…Furthermore, SGLT2is alleviate vascular permeability and mitochondrial Ca 2+ overload [ 99 ]. According to the study of Osaka et al, hyperglycaemic-stimulated NHE-1 activity was reversed via luseogliflozin in mice cardiomyocytes, which resulted in the attenuation of TGF-β2 expression and mitigation of cardiomyocyte hypertrophy and fibrosis [ 102 ].…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…According to KEGG pathway analysis, the 6 signaling pathways enriched by tRF-21-NB8PLML3E are mainly related to metabolism. It is generally accepted that the disorder of the cardiac metabolic process is the common pathogenesis factor of PCH [29,30]. It has been shown that impaired adaptation of energy metabolism can exacerbate pathological hypertrophy and increase cardiomyocyte death [31].…”
Section: Discussionmentioning
confidence: 99%